AUDIT QUALITY DURING THE COVID-19 PANDEMIC - Hansel Widyadhana; Yie Ke Feliana (SEAN Institute, 2023)
The COVID-19 pandemic has clearly become a challenge for all sectors to undergo a new normal, including auditors. KAP has made many adjustments during the audit process during the pandemic. This adjustment includes audit procedures, employment, and work culture. Researchers want to know how audit quality is during the Covid-19 pandemic. In this study the researchers positioned themselves as participant observers and conducted observations and interviews with KAP X employees. Researchers observe that during a pandemic, auditors will be vulnerable to audit bias. The researcher succeeded in concluding several audit biases and how the influence of each of these biases affects audit quality and concludes several aspects of the auditor's self, such as the right to disconnect, which can affect audit quality The audit quality factor emphasized in this study is more towards internal factors, namely the auditor himself. The researcher raises the audit bias factor as one aspect that arises from within the auditor.